Law Enforcement as Discretion and Legal Process - Makogon, Boris V.; Aristov, Evgeniy V.; Chaban, Evgeniy A.; Fedorov, Maxim V.; Umarova, Madina A. (International Journal of Criminology and Sociology, 2022)
Coercive authority is central to the law inforcement, and the discretionary use of police authority is a decision-making process, as officers evaluate the situations in which they intervene and choose a course of action from among a set of alternatives. This article investigates the analytical and synthesis aspects of a wide range of sources, considering law enforcement from a dual perspective: as legal discretion and as a kind of legal process. This research applied the classical methodology of qualitative analysis of systems and processes, in particular, a system-analytical approach to the study of research objects. In conclusion, the role of law enforcement in the modern state-legal reality and the place of mandatory features of the legal process in the law enforcement structure is presented. Based on the study, it can be stated that The role of the procedural form is primarily that following its requirements will guarantee the objectivity and efficiency of law enforcement.